The emerging phenomenon of electronic cigarettes. (February 2012) - Caponnetto, Pasquale; Campagna, Davide; Papale, Gabriella; Russo, Cristina; Polosa, Riccardo
The need for novel and more effective approaches to tobacco control is unquestionable. The electronic cigarette is a battery-powered electronic nicotine delivery system that looks very similar to a conventional cigarette and is capable of emulating smoking, but without the combustion products accountable for smoking''s damaging effects. Smokers who decide to switch to electronic cigarettes instead of continuing to smoke would achieve large health gains. The electronic cigarette is an emerging phenomenon that is becoming increasingly popular with smokers worldwide. Users report buying them to help quit smoking, to reduce cigarette consumption, to relieve tobacco withdrawal symptoms due to workplace smoking restrictions and to continue to have a 'smoking'' experience but with reduced health risks. The focus of the present article is the health effects of using electronic cigarettes, with consideration given to the acceptability, safety and effectiveness of this product to serve as a long-term substitute for smoking or as a tool for smoking cessation.